2019
DOI: 10.1038/s41598-019-49215-9
|View full text |Cite
|
Sign up to set email alerts
|

The expression of PD-L1 in salivary gland carcinomas

Abstract: Objective was to analyze the role of PD-L1 and its relation to demographic, patho-clinical and outcome parameters in salivary gland carcinoma (SGC) patients. Patients treated for salivary gland carcinomas between 1994 and 2010 were included. A retrospective chart review for baseline characteristics, pathohistological, clinical and outcome data was performed. Immunohistochemistry for PD-L1 was performed using tissue microarrays. PD-L1 expression was assessed in tumor cells and tumor-infiltrating immune cells (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 47 publications
3
52
0
7
Order By: Relevance
“…The clinicopathological characteristics of the investigated cohort were comparable to the results from other studies, even though the proportion of AC, NOS was slightly higher when compared to other cohorts [16]. Patients with AC, NOS presented at higher age and a higher frequency of metastatic disease is in line with previous reports [19,20].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The clinicopathological characteristics of the investigated cohort were comparable to the results from other studies, even though the proportion of AC, NOS was slightly higher when compared to other cohorts [16]. Patients with AC, NOS presented at higher age and a higher frequency of metastatic disease is in line with previous reports [19,20].…”
Section: Discussionsupporting
confidence: 89%
“…In line with that, a majority of AC, NOS (67%) cases was scored with IC values of 2 or 3, which highlights the tumor area covered by PD-L1 positive immune cells. In the recent study from Vital et al, the authors found a higher frequency of PD-L1 + MEC compared to AC, NOS, AdCC, and ACC [16]. However, given the fact that the authors used a different antibody clone (SP142) and adapted the cutoff of 1% PD-L1 + tumor cells that had initially been reported for NSCLC and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most SDC cases are microsatellite‐stable and have a low TMB 59,63,70,73,82 . There are no consistent data on PD‐L1 expression 59‐64 . A study of immune checkpoint inhibitor (pembrolizumab) treatment for advanced salivary gland carcinoma reported a 12% response rate, and another study of pembrolizumab included 1 SDC case in the cohort 109,110 .…”
Section: Treatmentmentioning
confidence: 99%